무산동 안저 사진기로 진단된 당뇨망막병증 위험 요인 분석: 제5기 국민건강영양조사 자료 - 윤정석(Jung Suk Yoon), 백승국(Seung-Kook Baek), 이영훈(Young Hoon Lee) (Daihan angwa haghoi jabji, 2019)
목적: 당뇨망막병증과 관련한 인구사회학적 요소, 건강관련행위 및 건강 상태 요소, 당뇨병 관련 요소와의 관계를 밝히고 현재 건강검진에서의 개선점을 제시하는 데에 목적이 있다. 대상과 방법: 제5기 국민건강영양조사를 완료한 19세 이상의 성인 중 당뇨병을 진단받고 무산동 안저촬영을 시행한 1,444명을 대상으로 연구를 진행하였다. 당뇨망막병증의 진단은 modified Airlie House classification에 따라 정의하였다. 조사 대상자들은 인구사회학적 요소, 건강관련행위 및 건강상태 요소, 당뇨병 관련 요소에 따라 단변량 및 다변량 분석을 시행하였다. 결과: 연구대상자 1,444명 중 당뇨망막병증 군은 277명이었으며, 유병률은 19.18%였다. 당뇨망막병증의 위험도는 체질량 지수가 높을수록 0.92배 낮았다(p=0.001; 95% confidence interval [CI], 0.883-0.966). 당뇨병 유병기간이 길수록 위험도는 증가하였으며, 새로 진단받은 그룹에 비해 11년 이상 그룹은 26.025배 높았다(p<0.001; 95% CI, 10.840-62.482). 당화혈색소가 높을수록 위험도는 증가하였으며, 11.0% 이상 그룹은 6.0% 이하 그룹보다 위험도가 5.973배 높았다(p<0.001; 95% CI, 2.984-11.956). 인슐린 주사 사용 시 당뇨망막병증의 위험도가 2.050배 높았다(p=0.003; 95% CI, 1.284-3.275). 결론: 당뇨병 유병기간이 긴 경우와 당화혈색소가 높은 경우, 인슐린을 사용하는 경우의 환자군에서 당뇨망막병증 발생의 위험도가 높으므로, 이를 바탕으로 당뇨망막병증에 대한 맞춤형 결과 전달 및 교육, 조기검진이 이루어져야 할 것으로 사료된다. Purpose: To clarify the relationship between various factors (sociodemographic factors, health behavioral risk factors and health status, and diabetic factors) related to diabetic retinopathy and to suggest improvements regarding the associated medical examination. Methods: The subjects were 1,444 diabetic patients diagnosed in the 5th Korean National Health and Nutrition Examination Survey (KNHANES), aged 19 years or older, who underwent non-mydriatic fundus photography. The criteria for diagnosing diabetes were a fasting glucose level ≥ 126 mg/dL and a previous diagnosis of diabetes or currently undergoing treatment. The diagnosis of diabetic retinopathy followed the modified Airlie House classification. Univariate and multivariate analyses of diabetic retinopathy were performed. Results: Among the 1,444 patients who were diagnosed with diabetes, 277 had diabetic retinopathy; the prevalence rate was 19.18%. The higher the body mass index, the lower the risk of diabetic retinopathy by 0.924 times (p = 0.001; 95% confidence interval [CI], 0.883-0.966). The longer the duration of diabetes, the greater the risk of diabetic retinopathy; the prevalence period group of more than 11 years had a 26.025-fold higher risk than the newly diagnosed group (p < 0.001; 95% CI, 10.840-62.482). The risk of diabetic retinopathy increased with the hemoglobin A1c (HbA1c) level; the risk was 5.973-fold higher in the group with HbA1c above 11.0% (p < 0.001; 95% CI, 2.984-11.956) compared with the group with HbA1c < 6.0%. The risk of diabetic retinopathy was 2.050-fold greater with insulin injections (p = 0.003; 95% CI, 1.284-3.275). Conclusions: The risk of diabetic retinopathy was higher in patients with a longer duration of diabetes, a high HbA1c level, and in those using insulin. These findings highlight the need for early education and ophthalmologic examinations for at-risk patients. KCI Citation Count: 0